PENGARUH KUALITAS PRODUK, PELAYANAN DAN DESAIN WEB TERHADAP KEPUASAN KONSUMEN DALAM BERBELANJA ONLINE MELALUI SHOPEE (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa Yogyakarta) - Meri Ariani; Muinah Fadhilah; Putri Dwi Cahyani (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to examine the effect of product quality, service quality and web design on customer satisfaction. The sample used in this study is Shopee consumers who are students of the Faculty of Economics, University of Sarjanawiyata Tamansiswa. Sampling using purposive sampling method and obtained as many as 110 respondents. This study uses multiple regression analysis. The results showed that product quality had a positive effect on customer satisfaction. Service quality has no effect on customer satisfaction. Web design has a positive effect on customer satisfaction. Keywords: Product Quality; Service Quality; Web Design; Customer Satisfaction